Beyond the one-child policy: a response to Conly - Julian Roche (The White Horse Press, 2017)
The problems with Conly’s proposed ‘one-child’ policy are a good example of where the attempt to limit paternalism becomes self-defeating, and actually ends up potentially aiding the case against controlling population rather than promoting it, as well as negatively influencing the debate about paternalism more generally. There are many better potential ways of developing public policy towards population control than a ‘one-child’ policy that synchronise with richer ways to understand individual interests.